O poder normativo das agências reguladoras: a participação dos interessados no procedimento de produção normativa da Resolução 414/2010 da Agência Nacional de Energia Elétrica - ANEEL - LEAL, David Abdalla Pires (2017)
The exercise of the competences established in the Brazilian Constitution by the Brazilian Regulatory Agencies, especially in view of the concentration of functions that can be classified as typical by other powers of the Republic, in a single organ, have generated questions, especially when dealing with normative competence. The present work has the objective of analyzing whether the production procedure of Normative Resolution No. 414/2010, of the National Electric Energy Agency, can be considered as an inducer of legitimacy in light of the Theory of Legitimation by the Niklas Luhmann Procedure (1980). It was observed that the procedure adopted by ANEEL in the approval of Normative Resolution 414 of September 9, 2010 was sufficiently open to the flows of contributions of the most diverse groups of stakeholders, shaping the final product of the normative procedure and, thus, contributing To reduce the questions about this product, and it can be concluded that the procedure adopted can be considered as inducing legitimacy, in the form of the Theory of Legitimation by Procedure. Thus, it is clear that other mechanisms of legitimization are necessary in addition to those related to the function carried out by the agencies, such as those used in the context of this administrative procedure, which have allowed the establishment of an effective communication between the Regulatory State and the stakeholders of the most diverse categories, through The submission of contributions by the latter and of answers justified by the Agency, which allowed the procedure to be framed to the bases of the theory in question, since the procedure required the aptitude necessary to carry out structural changes in the expectations of those involved, reducing the possibility of not Acceptance of the state decision included in the resolution.